Therapeutic alliance and adherence to a plant-based eating plan to treat chronic disease - Michiel A van Zyl; Lesley M Harris (Cogent Social Sciences, 2017)
Background: Systematic reviews show that a plant-based diet offers many benefits to patients with a variety of chronic illnesses. However, more research is needed to show how plant-based diets are successfully prescribed by physicians and what supports are essential for adherence. The primary research questions in this study were: Is therapeutic alliance correlated with adherence to the eating plan?; Does a change in therapeutic alliance result in a change in adherence?; and How do patients view the doctor-patient relationship and adherence? Methods: This multiple methods feasibility study combined cross-sectional pre-post and six-month follow-up survey, a focus group and case study methodology. Results: Patients rated their relationship with their PCP as high, and most patients (78.3%) strictly adhered to the eating plan. Strictness in following the plan was positively correlated with therapeutic alliance (r = 0.346, p = 0.025). Both the PCP and the support group members attributed the doctor-patient relationship as central to the change process. Patients also emphasized their ownership of the plan, a supportive community environment and a positive change in health as motivation for adherence. Conclusion: Adherence rates, ameliorated by the doctor-patient relationship, indicated that the diet is a feasible option for the treatment of chronic disease.